In vivo screening for analgesic and anti-inflammatory activities of syngonium podophyllum L.: a remarkable herbal medicine - Hossain, Md Sarwar; Uddin, Md Sahab; Kabir, Md Tanvir; Akhter, Shammi; Goswami, Srijan; Mamun, Abdullah Al; Herrera-Calderon, Oscar; Asaduzzaman, Md D.; Abdel-Daim, Mohamed Mohamed (© 2017 SCIENCEDOMAIN international, 2018)
This article was published in the Annual Research and Review in Biology [© 2017 Hossain et al.] and the definite version is available at : http://doi.org/10.9734/ARRB/2017/35692 The Journal's website is at: http://www.sciencedomain.org/abstract/20787